2003
DOI: 10.1501/dishek_0000000027
|View full text |Cite
|
Sign up to set email alerts
|

Ai̇leni̇n Sosyoekonomi̇k Durumu Ve Eği̇ti̇m Düzeyi̇ni̇n Çocuklarda Dental Kaygi Üzeri̇ne Etki̇si̇

Abstract: Negative correlation was found between children's dental anxiety and socioeconomic status and education levels of the parents (p<0.05). According to the results of VPT, it was found that, boys were more anxious than girls in Group I (p<0.05). On the other hand, it was also determined that, girls were more anxious than boys according to the results of CFSS-DS in Group II (p<0.05).As a result, it is thought that, socioeconomic status and education levels of the parents and gender of children were important assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
7

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
1
0
7
Order By: Relevance
“…In their study, the 3-6 years age group children had more dental anxiety [37]. Taani et al (2005) found that girls were more likely to have higher levels of fear than boys on 1021 children aged 12-15 years in Jordan [ 38].Similarly, Önçağ and Çoğulu (2005) found that the dental fear level of girls was higher than in boys on 120 children aged 3-12 years who applied to the Pedodontics Clinic, using the Child Fear Rating Scale (CFSS-DS) [39]. Oba et al (2009) reported that the highest score (45.8 ± 10.061) was 7 years old and the lowest score (38.0 ± 0.00) was 11 years old in the study conducted by using the Child Fear Rating Scale (CFSS-DS) with 275 children aged 7-11 in a primary school in Kırıkkale , the difference was found to be significant [33].In our study, the difference between the mean scores of the general scale of the children aged 7-9 (45.46 ± 11.87) and the other age groups was statistically significant (p <0.05) in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the 3-6 years age group children had more dental anxiety [37]. Taani et al (2005) found that girls were more likely to have higher levels of fear than boys on 1021 children aged 12-15 years in Jordan [ 38].Similarly, Önçağ and Çoğulu (2005) found that the dental fear level of girls was higher than in boys on 120 children aged 3-12 years who applied to the Pedodontics Clinic, using the Child Fear Rating Scale (CFSS-DS) [39]. Oba et al (2009) reported that the highest score (45.8 ± 10.061) was 7 years old and the lowest score (38.0 ± 0.00) was 11 years old in the study conducted by using the Child Fear Rating Scale (CFSS-DS) with 275 children aged 7-11 in a primary school in Kırıkkale , the difference was found to be significant [33].In our study, the difference between the mean scores of the general scale of the children aged 7-9 (45.46 ± 11.87) and the other age groups was statistically significant (p <0.05) in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde dental anksiyetenin CFSS-DS skalası ile değerlendirildiği çalışmalar mevcuttur (17)(18)(19)(20). Bu çalışmalara benzer şekilde sunulan çalışmada da CFSS-DS skorları değerlendirilirken 2 adet sınır (cut-off) puan belirlenmiştir.…”
Section: Tartiġmaunclassified
“…Kaygı ve Korku Kavramları Kaygı ve korku, organizma için tehlike sayılabilecek bir durum karĢısında savunma mekanizmalarını harekete geçiren duygulardır . Korku, yaĢamı veya güvenliği tehdit eden mevcut veya olası bir tehlikeye karĢı gösterilen, ruhsal ve bedensel olarak verilen bir reaksiyondur 7,8 . Weinstein ve arkadaĢları 9 ; korkunun, kalıtsal olmamasına rağmen, bulaĢıcı olarak yayıldığını, kiĢinin korkularını fobi haline dönüĢtürmesiyle sürekli hale getirdiği, önceki olumsuz deneyimlerin sebep olduğu istenmeyen hallerin müdahalesinde erken çocukluk dönemine inilmesi gerektiğini bildirmektedirler.…”
Section: Kronolojik Yaş Dönemlerine Göre çOcuk Davranış Larıunclassified
“…DiĢ hekimine baĢvuran bireylerin kaygı ve korkusunun olup olmadığının tedavi öncesi belirlenmesi , hekimin tedavi sırasında karşılaşabileceği tepkilere hazırlıklı olmasına ve hastanın kaygı ve korku düzeyinin azaltılmasına ilişkin birtakım önlemlerin alın masına olanak sağlamaktadır 7,49 . DiĢ hekimi kaygı ve korkusunun tüm boyutlarının ortaya çıkartılarak doğru bir şekilde değerlendirilmesi gerekmektedir .…”
Section: Diģ Hekimi Kaygı Ve Korkusunun Skalalarla Belirlenmesiunclassified
See 1 more Smart Citation